T8. ATHEROGENIC LIPID RATIOS RELATED TO MYELOPEROXIDASE AND C-REACTIVE PROTEIN LEVELS IN PSYCHOTIC DISORDERS. (9th April 2019) - Reponen, Elina; Dieset, Ingrid; Tesli, Martin; Mørch, Ragni H; Steen, Nils Eiel; Hope, Sigrun; Vedal, Trude S J; Aas, Monica; Szabo, Attila; Gohar, Sherif M; Wedervang-Resell, Kirsten; Melle, Ingrid; et al.
Abstract: Background: Cardiovascular disease (CVD) is a major cause of premature death in patients with psychotic disorders. The interaction between lipid accumulation, inflammation and vascular remodeling promotes atherogenesis and adverse CVD outcomes. We hypothesize that inflammatory markers reflecting different inflammatory pathways with relevance for atherogenesis are associated with CVD risk in patients with psychotic disorders. Here we investigate general and stable down-stream markers of inflammation (high-sensitivity C-reactive protein, hs-CRP; glycoprotein 130, gp130), vascular inflammation, calcification, and endothelial function (pentraxin 3, PTX3; osteoprotegerin, OPG; von Willebrand factor, vWF;), markers related to fibrosis and extra-cellular matrix remodeling (galectin-3. Gal3; cathepsin S, CatS), neutrophil activation and function (myeloperoxidase, MPO), and vascular apoptosis (insulin-like growth factor-binding protein 4, IGFBP4). Methods: We included 527 patients with schizophrenia spectrum disorders (SCZ), 288 patients with bipolar spectrum disorders (BD), and 95 healthy controls (HC). We measured fasting plasma levels of hs-CRP, PTX3, OPG, vWF, gp130, Gal3, CatS, MPO, and IGFBP4 in patients with psychotic disorders and HC. Differences between groups were analyzed by multivariate analysis of covariance adjusting for age, sex, and BMI. Cardio-metabolic risk was estimated using established atherogenic lipid ratios including total cholesterol/high-density lipoprotein-c (TC/HDL) and triglyceride/HDL (TG/HDL) using sex-dependent cut-offs, and differences in the proportion of individuals at risk between diagnostic groups was assessed using chi-square. Finally, in inflammatory markers that were elevated in patients (hs-CRP and MPO), the unadjusted and multivariable adjusted estimated atherogenic risk (i.e. based on lipid ratios) within the total patient population, and within diagnostic groups, was assessed using logistic regression, adjusting for age, sex, BMI, insulin resistance, smoking, systolic blood pressure and anti-psychotic treatment (defined daily dose; DDD). Results: The patient group as a whole had a markedly higher proportion with enhanced TC/HDL (26.2%) and TG/HDL (30.5%) compared to HC (9.2% and 8.2% for TC/HDL and TG/HDL, respectively). The adjusted risk for an elevated TC/HDL was 2.69 [CI 1.29–5.60] and for an elevated TG/HDL was 3.16 [CI 1.47–6.80]. SCZ and BD groups were characterized by markedly higher MPO compared with HC, and SCZ by higher levels of hs-CRP, in age, sex and BMI adjusted analyses. In contrast, lower gp130, Gal3 and CatS was observed in both patient groups while there were no significant differences for the remaining markers. In the patient group as a whole, the adjusted risk for having an atherogenic TC/HDL ratio was 1.39 [CI 1.11–1.74] and 1.25 [CI 1.04–1.52] per SD increase in CRP and MPO, respectively. For having an elevated TG/HDL, the adjusted risk was 1.34 [CI 1.07–1.67] for a 1SD increase in CRP. These associations were more prominent in SCZ. Discussion: Patients with psychotic disorders have a markedly higher CVD risk as reflected by atherogenic lipid ratios. The increased risk is associated with higher plasma levels of CRP and MPO suggesting that low-grade inflammation in combination with abnormal neutrophil activation may cause the increased CVD risk in these patients. Activated neutrophils release reactive oxygen species promoting oxidation of lipoproteins, which could contribute to oxidative stress and atherogenesis.